Naturally Occurring Bioactives as Antivirals: Emphasis on Coronavirus Infection - Seyed Abdulmajid Ayatollahi; Seyed Abdulmajid Ayatollahi; Seyed Abdulmajid Ayatollahi; Javad Sharifi-Rad; Patrick Valere Tsouh Fokou; Gail B. Mahady; Hafiz Ansar Rasul Suleria; Shivani Krishna Kapuganti; Kundlik Gadhave; Rajanish Giri; Neha Garg; Rohit Sharma; et al. (Frontiers Media S.A., 2021)
The current coronavirus disease (COVID-19) outbreak is a significant threat to human health and the worldwide economy. Coronaviruses cause a variety of diseases, such as pneumonia-like upper respiratory tract illnesses, gastroenteritis, encephalitis, multiple organ failure involving lungs and kidneys which might cause death. Since the pandemic started there have been more than 107 million COVID-19 infections caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and ∼2.4 million deaths globally. SARS-CoV-2 is easily transmitted from person-to-person and has spread quickly across all continents. With the continued increase in morbidity and mortality caused by COVID-19, and the damage to the global economy, there is an urgent need for effective prevention and treatment strategies. The advent of safe and effective vaccines has been a significant step forward in the battle against COVID-19, however treatment of the symptoms associated with the disease still requires new anti-viral and anti-inflammatory drug therapies. To this end, scientists have been investigating available natural products that may be effective against SARS-CoV-2, with some products showing promise in fighting several viral infections. Since many natural products are dietary components or are prepared as dietary supplements people tend to consider them safer than synthetic drugs. For example, Traditional Chinese Medicines have been effectively utilized to treat SARS-CoV-2 infected patients with promising results. In this review, we summarize the current knowledge of COVID-19 therapies and the therapeutic potential of medicinal plant extracts and natural compounds for the treatment of several viral infections, with special emphasis on SARS-CoV-2 infection. Realistic strategies that can be employed for the effective use of bioactive compounds for anti-SARS-CoV-2 research are also provided.